2006
DOI: 10.1254/jphs.cpj06010x
|View full text |Cite
|
Sign up to set email alerts
|

A New Frontier in Epilepsy: Novel Antiepileptogenic Drugs

Abstract: Abstract. Epilepsy is a hetergenous syndrome characterized by recurrently and repeatedly occurring seizures. Although able to inhibit the epileptic seizures, the currently available antiepileptic drugs (AEDs) have no effects on epileptogenesis. Such AEDs should be classified as drugs against ictogenesis, which are transient events in ion and / or receptor-gated channels related with triggering to evoke seizures. Epileptogenesis involves long-term and histological / biochemical/ physiological alterations formed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
20
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 56 publications
1
20
0
Order By: Relevance
“…About one-third of patients with TLE are pharmacoresistant and do not respond to current treatments (Sasa, 2006).Therefore, much effort has been put towards finding new treatments for drug resistant epilepsy. Such efforts have led to development of the repetitive transcranial magnetic stimulation (rTMS) as an alternative therapy for pharmacoresistant epileptic patients (Kimiskidis, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…About one-third of patients with TLE are pharmacoresistant and do not respond to current treatments (Sasa, 2006).Therefore, much effort has been put towards finding new treatments for drug resistant epilepsy. Such efforts have led to development of the repetitive transcranial magnetic stimulation (rTMS) as an alternative therapy for pharmacoresistant epileptic patients (Kimiskidis, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…l-1 serves as a key intermediate for the production of the antituberculosis drug ethambutol [19] and the antiepileptic drug levetiracetam. [20] In this study, the production process consists of two enzymatic reactions as shown in Scheme 1: conversion of lthreonine (l-2) to 2-oxobutyrate (3a) by a threonine deaminase (TD) and asymmetric transfer of an amino group from benzylamine (4a) to 3a by an (S)-enantioselective w-TA. The net reaction employs l-2 and 4a as substrates, yielding ammonia, benzaldehyde (3b) and l-1.…”
Section: Introductionmentioning
confidence: 99%
“…However, 20–30% of the patients are refractory to therapies using currently available antiepileptic drugs ( Provini et al , 1999 ; Patsalos, 2000 ; Jiang et al , 2007 ). Epileptogenesis involves histological, biochemical and physiological alterations that, over time, alter the balance between excitatory and inhibitory neurotransmission in multiple brain structures ( Sasa, 2006 ). The excessive enhancement of excitatory neurotransmission and/or the reduction of inhibitory pathways, as well as the regulation of some signal transductions may cause seizures ( Gale, 1993 ; Tsuda et al , 1997 ; Zilles et al , 1999 ).…”
Section: Introductionmentioning
confidence: 99%